2007
DOI: 10.1177/0269881107078490
|View full text |Cite
|
Sign up to set email alerts
|

Selective serotonin re-uptake inhibitor treatment-emergent sexual dysfunction: randomized double-blind placebo-controlled parallel-group fixed-dose study of a potential adjuvant compound, VML-670

Abstract: Sexual dysfunction is common during acute and continuation treatment of depressed patients with selective serotonin (5-hydroxytryptamine, 5-HT) re-uptake inhibitors (ssRIs), but there is no consensus on clinical management. Compounds with 5-HT(1A) agonist properties have been proposed as adjuvant agents in patients continuing with ssRIs. Randomized double-blind placebo-controlled parallel-group fixed-dose 4-week treatment study. Previously depressed male or female patients in symptomatic remission receiving st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…While the present data strongly support 5-HT 1A antagonism as beneficial for improving SSRI-induced sexual dysfunction, preclinical data from other laboratories have reported that 5-HT 1A antagonism appears to exacerbate chronic SSRI-induced sexual deficits in rats (Ahlenius & Larsson, 1999 ;de Jong et al 2005 ;Looney et al 2005). Based on clinical evidence from both the recent failure of the 5-HT 1A agonist VML-670 to improve SSRI-induced sexual dysfunction (Baldwin et al 2008) coupled with the positive, albeit limited findings with buspirone that suggest that a 5-HT 1A partial agonist may improve SSRI-induced sexual dysfunction (Landen et al 1999 ;Norden, 1994), it is logical to speculate that reducing the intrinsic activity of compounds acting at the 5-HT 1A receptor from full agonists like VML-670 to partial agonists like buspirone, and potentially to antagonists, may be beneficial as adjunctive therapies for the treatment of SSRI-induced sexual dysfunction.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…While the present data strongly support 5-HT 1A antagonism as beneficial for improving SSRI-induced sexual dysfunction, preclinical data from other laboratories have reported that 5-HT 1A antagonism appears to exacerbate chronic SSRI-induced sexual deficits in rats (Ahlenius & Larsson, 1999 ;de Jong et al 2005 ;Looney et al 2005). Based on clinical evidence from both the recent failure of the 5-HT 1A agonist VML-670 to improve SSRI-induced sexual dysfunction (Baldwin et al 2008) coupled with the positive, albeit limited findings with buspirone that suggest that a 5-HT 1A partial agonist may improve SSRI-induced sexual dysfunction (Landen et al 1999 ;Norden, 1994), it is logical to speculate that reducing the intrinsic activity of compounds acting at the 5-HT 1A receptor from full agonists like VML-670 to partial agonists like buspirone, and potentially to antagonists, may be beneficial as adjunctive therapies for the treatment of SSRI-induced sexual dysfunction.…”
Section: Discussionsupporting
confidence: 59%
“…A small number of clinical trials evaluating adjunctive SSRI treatment with the 5-HT 1A partial agonist buspirone, have demonstrated an improvement in SSRI-induced sexual dysfunction (Landen et al 1999 ;Norden, 1994). However, a recent study by Baldwin et al (2008) concluded that an experimental 5-HT 1A agonist, VML-670 failed to reduce sexual dysfunction associated with SSRI treatment in depressed patients. These data contrast with the preclinical data for VML-670 which suggested that 5-HT 1A agonists may be effective in treating SSRIinduced sexual dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Augmentation with VML-670 (a 5-HT 1A receptor agonist), (n = 88) conferred no significant advantage over placebo (Baldwin et al, 2008). Augmentation with bupropion (n = 41) (DeBattista et al, 2005), (n = 30) (Masand, Ashton, Gupta, & Frank, 2001) or methylphenidate (Pae et al, 2009), also had no significant advantage on ASEX-scores.…”
Section: Treatment-emergent Sexual Dysfunction During Antidepressanmentioning
confidence: 97%
“…The novel antidepressant drug vilazodone, which has both selective serotonin reuptake inhibitor and 5-HT 1A partial agonist properties, appears to have a low incidence of adverse effects on sexual functioning [67, 68], as does the “multimodal” compound LuAA21004 (vortioxetine), whose pharmacological properties include full agonism at the 5-HT 1A receptor [69]. However, the experimental 5-HT 1A full agonist VML-670 was not efficacious in reversing sexual dysfunction associated with fluoxetine or paroxetine [70], and preclinical studies suggest that selective 5-HT 1A antagonists can both prevent and reverse fluoxetine-induced sexual dysfunction in rats [71]. …”
Section: Refined Approaches To Pharmacotherapymentioning
confidence: 99%